THE EFFECT OF A COMPOSITE MINERAL SORPTION-BARRIER LAYER ON MICROBIAL CONTAMINATION AND HATCHABILITY OF POULTRY HATCHING EGGS - N. Montayeva; A. Kereyev; G. Nagimova; F. Nurzhanova; A. Kozhayeva; N. Akatova (Animal Health and Biosafety, 2026)
The optimization of avian incubation remains a paramount objective within the global agro-industrial complex. This exhaustive research report presents a comprehensive English translation, seamlessly integrated with a deep structural and physiological analysis, of the original scientific investigation concerning the treatment of laying hen hatching eggs. The core investigation delineates the profound biological and thermodynamic effects of applying a composite mineral suspension—formulated from montmorillonite clay and opoka—to the surface of the eggshell prior to incubation. The primary objective of this research is to rigorously evaluate the efficacy of forming a functional "sorption-barrier layer" as a highly effective, ecologically safe, and sustainable alternative to traditional, highly toxic chemical disinfection methods. The empirical experiment was executed utilizing a precise methodology involving a control group and an experimental group, each comprising one hundred eggs, replicated twice to ensure statistical robusticity. The processing mechanism involved a transient, short-term immersion of the experimental eggs into the formulated mineral suspension, followed by a controlled ambient drying phase to establish the surface coating. Quantitative microbiological analysis established that the application of this composite mineral formulation guarantees a highly significant reduction in the microbial contamination of the eggshell surface. Specifically, the microbial load was suppressed from a baseline of (4.8–5.3) × 10³ colony-forming units per square centimeter (CFU/cm²) in the untreated control group down to an optimized (1.6–2.0) × 10³ CFU/cm² in the experimental cohort.